A Comparative Study of Natural Lighting Quality in Sharia Housing Based on Daylight Factor Evaluation Using Autodesk Revit - Angga Perdana (Universitas Atma Jaya Yogyakarta, 2023)
The Islamic residential concept is the famous tagline that several real estate developers chose for their housing products today; it attracts customer attention, primarily from the Muslim community. But only some housing products are suitable to all the ideal criteria of the Islamic Residential concept. Excellent Sharia housing must fulfill all Islamic residential concept requirements, including public facilities, open space, and building quality. The strategy of the ideal Islamic housing concept requirement is optimal natural light and ventilation in the entire room. The inner courtyard is one of the solutions to afford this strategy. The types of openings also affect the daylight penetration in a room. Autodesk Revit Simulation evaluates this research about the daylight factor aspect of Islamic housing in Sharia housing. The research method is a qualitative, quantitative, and comparatively mixed method. The minimum requirement of daylight factor for housing is 5%. The study object shows that in the case of Medina Residence 1, it sufficiently offers the most daylight factor affordability in a Sharia housing project. The research hypothesis is to maximize the daylight factor by modifying several types of windows and adding skylight openings to increase the daylight factor of the entire room. Increased wall window ratio and more inner open spaces are the solutions for the minimum size of the building site. In the case of Medina residence 1, the skylight opening can be applied, but the effect is less significant than making more openings facing the open space.